Globalism/localism at work - Beukema, Lena Margaretha, 1954-; Carrillo V., Jorge (Carrillo Viveros) (Amsterdam ; Boston : Elsevier JAI, 2004)
In this volume the focus is on the interrelations of the global and the local in their consequences for work. The process of restructuring of work is analyzed as an ongoing, locally situated process in which actors within work organizations play an important role. Nevertheless, when taking the context of work organizations into account, the increasing importance of the global on the local processes is obvious. Local practices keep their central importance, but the global doesn't function only as a context for the local anymore but forms more and more a practice of itself in which an increasing number of actors play their part.As we can see on the World Wide Web, people and firms are both emitters and receptors and act on the local and global level at the same time. Local diversity in a world with increasing interdependencies is shown in a number of contributions from different parts of the world. These contributions are clustered around two main themes: Labor markets in global and local scenarios - From industry to services; Global industries - Restructuring and local jobs. The many case studies presented shed light to the diversity that occurs in different local situations.
Handling global developments, shaping local practices: the interference of the global and the local in work restructuring / Leni Beukema and Jorge Carrillo -- New forms of industrial organization, regional development and the impact on work restructuring in Brazil / José Ricardo Ramalho -- Main labor changes in French car industry / Jean-Pierre Durand -- Segmentation of skills in the Mexican northern border: challenges in a globalized region / Alfredo Hualde -- Privatization and deregulation of telecommunications in Brazil: the global influence and local implications / Sonia Guimarães Larangeira -- Foreign direct investment and local linkages: the case of the Mexican television industry in Tijuana / Jorge Carrillo -- New deals in gambling: global markets and local regimes of regulation / Terry Austrin and Jackie West -- Global logistic chains as a result of local processes: the case of orchids / Leni Beukema and Harry Coenen -- Taking a seat in the global marketplace: opportunities for "high road" upgrading in the Indonesian wood furniture sector? / Anne Caroline Posthuma -- Work restructuring as ongoing glocal processes: concluding remarks / Leni Beukema.
Includes bibliographical references.
Description based on print version record.
Keywords: Industries -- Social aspects; Industrial organization; Globalization -- Social aspects; Globalization -- Economic aspects; Industrial location; Corporate reorganizations; Labor supply -- Effect of technological innovations on; Industries -- Social aspects -- Mexico; Industrial organization -- Mexico; Globalization -- Social aspects -- Mexico; Sociology: work & labour; Social Science -- Sociology -- General; Mexico -- Economic conditions -- 1994-